Axial Progenitors and the making of the Vertebrate Body Plan - Dias, André Miguel Gomes Duarte de Sousa (2022)
"The vertebrate body is laid down progressively in a head-to-tail sequence by dedicated axial progenitors with stem cell-like properties. The neuromesodermal competent population (NMC-population) contains progenitors with the potential to generate both neural (spinal cord) and mesodermal (e.g. somites) derivatives during axial elongation. In the mouse, this axial progenitor population arises at the end of gastrulation from the pluripotent epiblast, and lasts until somitogenesis is completed, contributing to the formation of the post-occipital body axis. In the first part of this thesis, using a single-cell ribonucleic acid sequencing (scRNA-seq) approach, we show that the characteristics of the mouse NMC-population change during axial elongation. In particular, we observed that these axial progenitors gradually lose epithelial features (e.g. loss of Cdh1 and Epcam) and concomitantly acquire some mesenchymal characteristics (e.g. increase of Cdh2 and Vim), displaying a wide range of epithelialmesenchymal plasticity (EMP) during trunk formation.(...)"